Why the Global Equity Allocation in Frontier Markets is Low ? Evidence from Vietnam - Joshi, Himanshu (Indian Journal of Research in Capital Markets, 2017)
Frontier countries accounted for 21.6% of the world's population, 6% of its nominal GDP, and only 3.1% of the world market capitalization. Thus, it is imperative that a global investor following indexing style of fund allocation should allocate 3.1% of its wealth in the frontier markets. However, a typical frontier market is characterized as highly volatile and illiquid. In addition to the volatility and illiquidity of the equity markets, impulsiveness of their currencies inflict heightened risk for the international investors. Thus, a case to case analysis of frontier markets makes sense for an active portfolio investor. The present paper explored the opportunities and challenges of equity allocation in frontier markets in general and Vietnam, in particular, evaluating their macroeconomic factors and investigating into the micro structure of their financial markets. The results suggested that there was a higher correlation of frontier markets and Vietnam market returns with the world market returns, coupled with low indigenous mean returns, high standard deviations, and coefficients of variance. This explained why there is lower allocation of global capital to the frontier markets in general and Vietnam in particular.